2021
DOI: 10.1080/17538947.2021.1953161
|View full text |Cite
|
Sign up to set email alerts
|

Input database related uncertainty of Biome-BGCMuSo agro-environmental model outputs

Abstract: Gridded model assessments require at least one climatic and one soil database for carrying out the simulations. There are several parallel soil and climate database development projects that provide sufficient, albeit considerably different, observation based input data for crop model based impact studies. The input database related uncertainty of the Biome-BGCMuSo agro-environmental model outputs was investigated using three and four different gridded climatic and soil databases, respectively covering an area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…Currently it is not the case in our study; therefore, it was not performed. Nevertheless, a recent study with Biome-BGCMuSo showed that the spatial variation in the SOC change rate is much larger than the variance in the SOC change rate originating from changes in model inputs (e.g., climate and soil data), for all investigated land uses (i.e., croplands, grasslands and forests) [92]. Accordingly, we can assume that the introduction of input data-related uncertainty at the plot level would not provide us with more information than we already obtained.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Currently it is not the case in our study; therefore, it was not performed. Nevertheless, a recent study with Biome-BGCMuSo showed that the spatial variation in the SOC change rate is much larger than the variance in the SOC change rate originating from changes in model inputs (e.g., climate and soil data), for all investigated land uses (i.e., croplands, grasslands and forests) [92]. Accordingly, we can assume that the introduction of input data-related uncertainty at the plot level would not provide us with more information than we already obtained.…”
Section: Discussionmentioning
confidence: 94%
“…Uncertainty analysis implies estimating the model result uncertainty originating from different model inputs and/or different model parameters [91]. Estimating the uncertainty originating from model inputs for Biome-BGCMuSo would assume possessing more than one climate and soil database covering the entire area of the investigation (i.e., the whole national territory) [92]. Currently it is not the case in our study; therefore, it was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…The second, normal simulation uses the results of the spinup simulation as initial conditions and runs for a given, predefined time period (Running and Gower 1991). Socalled transient simulation option (which is the extension of the spinup routine) is a novel feature in Biome-BGCMuSo in order to ensure smooth transition between the spinup and normal phase (Hidy et al, 2021).…”
Section: The Original Biome-bgc Modelmentioning
confidence: 99%
“…Below, we provide detailed description of the new developments that are included in Biome-BGCMuSo v6.2 which is the latest version released in September, 2021. A comprehensive review of the input data requirement of the model together with explanation on the input data structure is available in the User's Guide (Hidy et al, 2021). In this paper we refer to some input files (e.g.…”
Section: The Original Biome-bgc Modelmentioning
confidence: 99%
See 1 more Smart Citation